PEMANFAATAN LIMBAH ORGANIK UNTUK PEMBUATAN BRIKET SEBAGAI ENERGI ALTERNATIF UNTUK KEBUTUHAN MASYARAKAT DI DESA KULUR ILIR KABUPATEN BANGKA TENGAH - Eka Sari Wijianti; Saparin Saparin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2016)
Kulur Ilir is a village located in Lubuk Besar District, Central Bangka Regency, where the majority of the population, 63%, work as rubber, palm oil and pepper farmers. The large number of agriculture that develops in Kulur Ilir Village is also a very interesting potential for developing new innovations, namely making alternative energy briquettes using agricultural waste because most of the organic waste produced has not been utilized. Briquettes were developed to be one of the solutions to reduce the problem of community dependence on firewood, LPG gas and kerosene whose availability is getting thinner and cannot be renewed. The existence of the Universitas Bangka Belitung KKN-Tematik in Kulur Ilir Village regarding briquettes as alternative energy is expected to provide benefits to the community such as: the Kulur Ilir Village community can produce briquettes with raw materials in the village continuously both to meet personal needs and to be marketed, improve the economic level of the community through the briquette business, the community is no longer dependent on LPG gas and firewood whose availability is uncertain because they can use alternative energy, namely briquettes. as well as fostering an entrepreneurial spirit for anyone who wants to be an entrepreneur. As well as fostering an entrepreneurial spirit for anyone involved.